Galaxy Zoo: finding offset discs and bars in SDSS galaxies - Kruk, Sandor J.; Lintott, Chris J.; Simmons, Brooke D.; Bamford, Steven P.; Cardamone, Carolin N.; Fortson, Lucy; Hart, Ross E.; Häußler, Boris; Masters, Karen L.; Nichol, Robert C.; Schawinski, Kevin; Smethurst, Rebecca J. (Oxford University Press, 2017)
We use multiwavelength Sloan Digital Sky Survey (SDSS) images and Galaxy Zoo morphologies to identify a sample of ∼270 late-type galaxies with an off-centre bar. We measure offsets in the range 0.2–2.5 kpc between the photometric centres of the stellar disc and stellar bar. The measured offsets correlate with global asymmetries of the galaxies, with those with largest offsets showing higher lopsidedness. These findings are in good agreement with predictions from simulations of dwarf–dwarf tidal interactions producing off-centre bars. We find that the majority of galaxies with off-centre bars are of Magellanic type, with a median mass of 109.6 M⊙, and 91 per cent of them having M⋆ < 3 × 1010 M⊙, the characteristic mass at which galaxies start having higher central concentrations attributed to the presence of bulges. We conduct a search for companions to test the hypothesis of tidal interactions, but find that a similar fraction of galaxies with offset bars have companions within 100 kpc as galaxies with centred bars. Although this may be due to the incompleteness of the SDSS spectroscopic survey at the faint end, alternative scenarios that give rise to offset bars such as interactions with dark companions or the effect of lopsided halo potentials should be considered. Future observations are needed to confirm possible low-mass companion candidates and to determine the shape of the dark matter halo, in order to find the explanation for the off-centre bars in these galaxies.